Investment in Quality Upgrade and Regulation of the Internet - Edmond Baranes; Cuong Hung Vuong (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper studies the investment decision by a monopolistic internet service provider (ISP) in different regulatory environments. We consider that the ISP could technically provide separate quality upgrades to two vertically differentiated content providers (CPs); therefore, it could potentially extract the CPs' marginal profits through an offer to provide the quality upgrades. Our results show that if unregulated, the ISP optimally provides asymmetric quality upgrades, in favor of the high-quality CP. This subsequently increases the degree of content differentiation, softening competition between the CPs. Imposing a nondiscrimination regulation that forces the ISP to provide an equal quality upgrade to both CPs, however, can reduce the ISP.s investment incentive and social welfare. Furthermore, the investment level is higher if the regulated ISP is allowed to charge the CPs. Finally, a socially optimal investment can be opposite to the ISP's choice when the contents are enough substitutes.
Keywords: L13; L51; L96; 330; complementary; differentiation; investment; internet; regulation